An Interpolation from Avicenna’s The Canon of Medicine in the Ruthenian Translation of The Secret of Secrets - Temchin, Sergei (Slavistica Vilnensis, 2020)
The Ruthenian translation of the medieval treatise Secretum Secretorum (“The Secret of Secrets”) was made in Kiev during the second half of the 15th century from a Hebrew version that dates back to late 13th‒early 14th centuries, when it was translated from the Arabic original, which probably originated in its final form during the 10th century. The Ruthenian translation contains certain interpolations that had been already present in the Hebrew version before it was translated into Ruthenian. They had been extracted from several Arabic and Hebrew sources, such as the treatise Al-Mansuri by Abū Bakr Muhammad ibn Zakariyā al-Rāzī (865‒925) and the treatises On Poisons, On Coitus, and On Asthma by Maimonides (1135/1138‒1204).The author argues that the same Ruthenian translation also contains a minor (one-page long) interpolation that through Hebrew mediation goes back to The Canon of Medicine written in Arabic by Avicenna (980‒1037). It is still to be established which of the seven known Medieval Hebrew translations and/or the around 30 commentaries on it (all unpublished) was used as the immediate source for the Kievan translation. Nevertheless, the newly identified Arabic origin of this particular interpolation to the Ruthenian version of the treatise The Secret of Secrets sheds some light on the prehistory of this particular text’s portion and compliments the list of sources used by the Hebrew-to-Ruthenian translators in Kiev during the second half of the 15th century.
Keywords: literature of the Judaizers; Ruthenian translations from Hebrew; Great Duchy of Lithuania; The Secret of Secrets (Secretum Secretorum); Ibn Sina (Avicenna)